Implementasi profil pelajar Pancasila pada projek IPAS materi Indonesiaku kaya budaya dimensi gotong royong peserta didik kelas IV Sekolah Dasar - Dwijayanti, Mifta Nur Aini; Istiyati, Siti; Surya, Anesa (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
This research aims to (1) describe the planning, (2) describe the implementation, and (3) describe the evaluation of the implementation of the Pancasila student profile on the science and social studies project of the Indonesian cultural wealth material cooperation dimension of fourth grade students. This research uses a descriptive qualitative approach with a case study research design. The subjects in this study were fourth grade students at Karangasem 4 elementary school. Data collection techniques use the results of document study, observation, and interview. The data analysis technique uses Creswell analysis. The data validity test technique uses triangulation techniques. The research results showed that the planning for implementing the Pancasila student profile was 97%, the implementation was 89%, and the evaluation was 96%. The results of the mutual cooperation dimension of fourth grade students were cooperation by 50%, communication of common purpose by 50%, positive dependency by 42%, social coordination by 44%, responsiveness of the social environment by 40%, social perception by 47%, and sharing knowledge by 46%. Influencing factors are internal, namely the influence of individualism and egoism due to globalization, and external, namely differentiations of student characteristics and the teacher's lack of ability to guide small group discussions.